A history of the King in the sky: Balinese Kite Festival - Putu Bagus Anggaraditya (Bali Tourism Board, 2017)
‘Pelangi’ (Persatuan Layang-Layang Bali) or Bali Kite Association, held a kite flying festival from early July until the end of October 2017. It aims to preserve culture, stimulate creativity and grow bond and togetherness among societies as well as become a tourist attraction. Government supports the festival as means of cultural preservation as well as a tourist attraction for domestic and foreign. However, as time goes by, the land to play kite is getting narrower due to development. Therefore, attention and participation by local government and society are needed to maintain the availability of land for the sake of the preservation of this cultural festival.